Putting permanent grassland at the heart of a European agroecological transition: Findings and questions arising from the 'Ten Years for Agroecology' (TYFA) scenario. (29th November 2022) - Poux, Xavier; Aubert, Pierre‐Marie
Abstract: While the importance of permanent grasslands (PG) for the conservation of high nature value habitats is often acknowledged, their role in most of the main sustainable food system scenarios published in the last few years is less explicit. In the best case, the place of permanent grassland in scenarios and policy agendas is their conservation; in the worst one, they are simply replaced by afforested land or cropland, considered as a better option when the focus is on GHG emissions only. In this paper, we defend the idea that several misinterpretations of the positive and negative impacts of ruminants, the 'natural' users of PG, explain why ruminants are poorly addressed by most scenarios. Based on the findings of an agroecological scenario for Europe—TYFA, standing for Ten Years For Agroecology—in which extensive permanent grassland and ruminants together play a prominent role for biodiversity conservation, nitrogen cycling and climate change mitigation and adaptation, we call for a research agenda that would better inform the specific role of PG in the provision of ecosystem services—and in particular those that depend on nitrogen management.